Determination of Reservoir Ecosystem Status in Cimahi City Govenrment Office - Eka Wardhani; Faza Kamilah Kusnadi; Athaya Zahrani Irmansyah; Dian Noor Handiani (Universitas Diponegoro, 2024)
Cimahi City continues to try to repair the damaged reservoir to function optimally as a raw water reservoir. This effort requires identifying the status of the reservoir ecosystem by assessing three standard criteria: aquatic, boundary, and terrestrial quality status. Two methods were carried out: field observation and laboratory research. The field observations are observations and interviews, determining the water sampling point and water sampling, and aerial photography for mapping surveys. The parameters of chlorophyll-A, algae, total nitrogen, and total phosphate were analyzed for the laboratory research. Based on research, the status of aquatic is in the threatened-destruction category because trophic level includes hyper-eutrophic, moderately polluted water quality, low biodiversity, and loss of food webs. The quality of the boundary ecosystem is in the damaged category because >25% of the area of the boundary is a settlement, and there is the disposal of domestic waste that enters the reservoir through canals. The quality of terrestrial ecosystems is in the threatened-damaged category because the land vegetation in the water catchment area is low, and there is an average annual siltation of ≥2% of the depth of the reservoir. It was concluded that management must be carried out in the water catchment area.